Increase in Fish Production Through Bottom-Up Trophic Linkage in Coastal Waters Induced by Nutrients Supplied via Submarine Groundwater - Fujita, Koji; Shoji, Jun; Sugimoto, Ryo; Nakajima, Toshimi; Honda, Hisami; Takeuchi, Masaru; Tominaga, Osamu; Taniguchi, Makoto (Frontiers in Environmental Science, 2019)
Submarine groundwater is richer in nutrients compared to surface (river) water and therefore has been considered to be an essential component of biological production in marine coastal ecosystems. However, there has been no information on the effects of submarine groundwater on animals at high-order trophic levels. Here we show the first direct evidence that fish feeding and growth are elevated by submarine groundwater discharge (SGD) by on-site experiments and quantitative sampling. An experiment using cages moored on the sea bottom confirmed that the fishes obtained elevated levels of nutrition in the vicinity of SGD. Quantitative sampling at three sites with different hydrodynamic properties showed correspondence of high SGD with high biological production or biomass from producer to secondary consumers. These findings demonstrate nutrients of terrestrial origin provided via submarine groundwater in coastal areas promote marine fish production.